2016
DOI: 10.1177/0333102416646760
|View full text |Cite
|
Sign up to set email alerts
|

Putative role of 5-HT2B receptors in migraine pathophysiology

Abstract: Objective In this review we attempt to characterize the acute and chronic role of 5-HT receptors with regard to meningeal nociception in animal experiments and clinical data targeting migraine therapy. Background Migraine is a common disabling neurovascular primary headache disease, the pathomechanism of which is still unclear. Serotonin (5-HT) and its receptors might play an important role in some aspects of migraine pathogenesis. The ability of the unselective 5-HT receptor agonist m-chlorophenylpiperazine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 71 publications
0
13
0
1
Order By: Relevance
“…An involvement of 5-HT1B/D receptor is unlikely since sumatiptan alone or with mCPBG failed to activate firing. Thus, the role of receptors other than 5-HT1B/D, for instance, 5-HT2 receptor (Segelcke and Messlinger, 2016) should be studied in future experiments.…”
Section: Discussionmentioning
confidence: 99%
“…An involvement of 5-HT1B/D receptor is unlikely since sumatiptan alone or with mCPBG failed to activate firing. Thus, the role of receptors other than 5-HT1B/D, for instance, 5-HT2 receptor (Segelcke and Messlinger, 2016) should be studied in future experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Further, whereas we have reported that over-the-counter drug "NARON ACE ® ", which contained ETZ, exerted very good clinical performance for headache symptoms 1) , there are no studies focused on the pathogenesis of headache. For example, it has been suggested that in the rat model of migraine, the 5HT 2B receptor localized on the vascular endothelial cells of the dura matter has an important role in meningeal neurogenic inflammation 35,36,37) . Furthermore, the 5HT 2B receptor expressed in the trigeminal ganglionic cells of mice 21) could be assumed to have a role in the pain processing of trigeminal afferents.…”
Section: Biological and Pharmaceutical Bulletin Advance Publicationmentioning
confidence: 99%
“…Pharmacologic and genetic studies indicate that 5-HT2B is required for 5-HTmediated pathologies like PAH 17,43 , dermal, lung and liver fibrosis 19,44,45 , cardiac hypertrophy 46,47 , and mediates the valvular heart disease (VHD) and fibrosis associated with carcinoid syndrome 48 . Importantly, anti-migraine drugs like methysergide and ergotamine 49,50 , general anesthetics 51 , fenfluramine and conventional SSRIs [52][53][54][55] , and even the dopamine agonists and anti-parkinsonian drugs pergolide and cabergoline 50,56,57 , exert potent off-target effects on 5-HT2B 50 . In fact, 5-HT2B appears to be required for the therapeutic actions of SSRI 54 .…”
Section: Introductionmentioning
confidence: 99%